Analysis of elastic properties of lithium substituted barium vanadate glasses to understand the structural changes. (2021) - Goel, Parul; Honnavar, Gajanan V
Abstract: The elastic moduli of 60V2 O5 - (40-x) BaO-xLi2 O where x = 30, 25, 20, 15, 10 (mol%) glass system was analyzed and correlated with the physical properties of glass-like molar volume and average stretching force constant. This was done to understand how the rigidity of glass is affected by the variation in Li2 O content in the glass samples. This study involves the application of Makishima-Mackenzie's theory to calculate the elastic constants of glass, like Young's modulus, Bulk modulus, Modulus of rigidity and Poisson's ratio and correlate them to the structural modifications in the glass with the addition of alkali oxide (Li2 O) in the glass system at the expense of alkaline-earth oxide (BaO). This work was done to understand how the variation in the composition of glass affects its rigidity and elastic properties which in turn affects its structure. This study helped to tweak the mechanical properties of the current glass system by varying their chemical composition. It was found that glass with 30% Li2 O has the highest value of elastic constants and therefore, maximum mechanical strength.